Association of mechanical bowel preparation with oral antibiotics and anastomotic leak following left sided colorectal resection: an international, multi‐centre, prospective audit. (25th September 2018) - ,
Abstract: Introduction: The optimal bowel preparation strategy to minimise the risk of anastomotic leak is yet to be determined. This study aimed to determine whether oral antibiotics combined with mechanical bowel preparation (MBP+Abx) was associated with a reduced risk of anastomotic leak when compared to mechanical bowel preparation alone (MBP) or no bowel preparation (NBP). Methods: A pre‐planned analysis of the European Society of Coloproctology (ESCP) 2017 Left Sided Colorectal Resection audit was performed. Patients undergoing elective left sided colonic or rectal resection with primary anastomosis between 1 January 2017 and 15 March 2017 by any operative approach were included. The primary outcome measure was anastomotic leak. Results: Of 3676 patients across 343 centres in 47 countries, 618 (16.8%) received MBP+ABx, 1945 MBP (52.9%) and 1099 patients NBP (29.9%). Patients undergoing MBP+ABx had the lowest overall rate of anastomotic leak (6.1%, 9.2%, 8.7% respectively) in unadjusted analysis. After case‐mix adjustment using a mixed‐effects multivariable regression model, MBP+Abx was associated with a lower risk of anastomotic leak (OR 0.52, 0.30–0.92, P = 0.02) but MBP was not (OR 0.92, 0.63–1.36, P = 0.69) compared to NBP. Conclusion: This non‐randomised study adds 'real‐world', contemporaneous, and prospective evidence of the beneficial effects of combined mechanical bowel preparation and oral antibiotics in the prevention of anastomotic leak following left sided colorectal resection across diverse settings. We have also demonstrated limited uptake of this strategy in current international colorectal practice. Abstract : See page27–32 for full print list. All collaborating authors will be listed in the online edition, and be PubMed citable